The influence of excessive use of social media - Ariella Christ Maharani (Indonesian Journal of Social Sciences, 2021)
Technology that is overgrowing makes the audience increasingly spoiled with the existing features, including social media, which is a part of today's technological advances. Many platforms offer features that make users even more interested in sharing their excellent routines on these platforms. However, excessive use of social media and poor use harms users. One of the problems that result from overuse and poor use is the increasing incidence of depression. Individuals who experience depression tend to feel insufficient, and a feeling of wanting to end their life arises. Hence, it is necessary to know the causes and solutions to reduce the impact of excessive use of social media. This research method is quantitative. Researchers shared questionnaires to 101 respondents who were social media users aged at least 15 years. The results of this study indicate that most respondents tend to experience mood changes when using social media. That can occur because of jealousy when seeing content on their social media. Therefore, social media users must control their use of social media, for example, by being optimistic, doing fun activities, and increasing their religiosity.